(untitled) (Research, Society and Development, 2022)
This work The use of ludic games in the teaching-learning process in chemistry classes is a way found by teachers to make teaching more attractive and inserted in the students’ daily lives. Thus, this work presents a research on didactic games in chemistry teaching, whose objective was to analyze the process of application and validation of didactic games of chemistry, proposed for high school students, and how these games can influence teaching-learning of Chemistry. The methodology used as an evaluation process were two questionnaires with fourteen questions each; the questionnaires were applied before and after the ludic activity; the ludic activity related to hydrocarbons and organic functions was Organic Dominó. The game was applied in the 3rd grade of High School at EEEFM Padre Salvador Traccaiolli, located in the municipality of Castanhal, State of Pará. It is concluded that the use of didactic games is a teaching instrument that facilitates learning by awakening the student’s interest and motivating him to learn in a more pleasurable way. The Organic Dominó game motivated learning, as students recognized it as a pleasant alternative to the routine of expository classes, as well as stimulating to help in fixing the content studied.